Sub-bacia do Alto Piranhas, Sertão paraibano: percepção ambiental e perspectivas na gestão dos recursos hídricos. - Freitas, Maria Isabel Alves de (2012)
The Water Resources Management can be defined as the set of actions aimed at regulating the use, control and protection of water resources in accordance with relevant legislation and standards. Proper management of water resources becomes even more necessary in semiarid regions, which present peculiarities as the occurrence of irregular rainfall and high evaporation rates that affect the regime of rivers, affecting water availability in these areas. This study aimed to analyze the environmental aspects in communities within the river basin of the High Piranhas, in the backlands of Paraiba, order to provide insight in proposing programs to manage water resources in the region. The present study sought to analyze the environmental aspects in communities within the river basin of the Alto Piranhas in the Sertão of Paraíba, aiming to contribute subsidies to propose programs for managing water resources in the region. For the study, we used the theoretical and methodological assumptions of qualitative research as having methodological orientation Phenomenology. The techniques of data collection were participant observation and semistructured interviews. The research revealed a strong emotional attachment and dependence among social actors, their respective communities and water reserves present in them. Regarding the actions of administrative agencies, they showed up without a specific character continuous work and do not integrate the various social, economic and political problems inherent environmental. There is an interaction between the spheres of government, each level of government works individually, without a partnership or a dialogue between them. Regarding the study of environmental perception of the social actors involved, this helped in understanding the forms of natural resource use, conducted in communities. Thus, from the analysis of these interrelationships within the sub-basin of the Alto Piranhas was possible to list strategic actions, which may contribute to better management of water resources in the area. It is believed that this study contributed to the theoretical discussion of participatory management of water resources in the sertão of Paraiba. It is expected therefore that the information contained in this work will provide insight for future management plans consistent with local realities.